Phyllosphere microbiome responses to nano-berberine and chemical fungicides in powdery mildew infected strawberry - Yang, Meng; He, Tao; Moukarzel, Romy; Li, Man; Li, Mei; Zhang, Zengxiu; He, Yiyi; Liu, Yixiang; Yu, Lei; Zhu, Shusheng; Du, Fei (Frontiers in Plant Science, 2025)
Strawberry powdery mildew, caused by the obligate biotroph Podosphaera aphanis, is a major threat to commercial strawberry production, reducing both yield parameters and fruit quality. While chemical fungicides remain a standard control method, their non-target effects on phyllosphere microbial communities have raised important ecological and environmental concerns. Nano-pesticides are increasingly applied in plant disease management, however, their influence on the composition and functional potential of phyllosphere microbial communities remains poorly understood. The nano-berberine formulation (BBR-M) used in this study was provided by a collaborative group, with synthesis and physicochemical characteristics consistent with those previously reported for this material. In this study, we compared the field-level effects of a nano-berberine formulation (BBR-M) and conventional chemical fungicides (e.g., bupirimate) on the strawberry phyllosphere microbiota using high-throughput sequencing, bioinformatics analysis, and microbial isolation techniques. The results showed that nano-fungicide application significantly reduced the disease index of powdery mildew and markedly decreased its incidence in field-grown strawberries, ultimately lowering leaf disease incidence to 5.06% with a control efficacy of 96.81%. Furthermore, nano-fungicides and conventional chemical fungicides treatments were associated with distinct impacts on the phyllosphere microenvironment of strawberry. Application of BBR-M was associated with a more structured and potentially stable microbial community, characterized by increased fungal diversity and higher modularity in co-occurrence networks. In contrast, bupirimate treatment increased microbial complexity but coincided with reduced network stability. A strain of Bacillus siamensis—a genus identified as a core taxon within the BBR-M phyllosphere network—was subsequently isolated from nano-berberine–treated leaves and exhibited strong antagonistic activity against Colletotrichum nymphaeae. Field assays showed that this strain effectively suppressed strawberry powdery mildew with 98.18% control efficacy. Collectively, these findings provide important insights into the ecological safety and functional implications of novel pesticide technologies, underscoring the potential of nano-fungicides and native biocontrol agents for sustainable strawberry disease management.